Faktor-Faktor Yang Mempengaruhi Pengembangan Sistem Informasi Akuntansi: Kemajuan Teknologi, Pengetahuan Manajer Dan Partisipasi Pengguna - Amanda Nurmaulida; Cris Kuntadi; Rachmat Pramukty (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Previous or relevant research in scientific studies or publications is very important. Theories and phenomena of the relationship or influence between variables are strengthened by previous research or relevant research. This article examines the variables that influence the development of accounting information systems, including technological advances, manager knowledge, and user participation. It also includes literature on accounting information systems. The purpose of this article is to develop hypotheses about how different variables interact that can be applied to future research. The results of this article's literature review are: 1) technological advances have an effect on the development of accounting information systems; 2) the knowledge of managers influences the development of accounting information systems; and 3) user participation influences the development of accounting information systems.